FIRST RECORD ON ODONTANTHIAS FLAGRIS YOSHINO AND ARAGA, 1975 (PERCIFORMES: SERRANIDAE) IN INDONESIAN WATERS - Peristiwady, Teguh (Marine Research in Indonesia, 2011)
Two specimens of Odontanthias flagris have been caught from Bitung, North Sulawesi in June 2010. Previously, nown locations of this species are Okinawa and Nishino-shima, Japan. O. flagris is very similar with O. rhodopeplus. They shares following characters: dorsal fin rays X, 13; anal fin rays III, 7; pectorals fin rays 17-18; scales above lateral line 7; scales below lateral line 19 and gill rakers on lower limb 28. Characters differing O. flagris from O. rhodopeplus, O. chrysostictus and other six species appear in the percentage of orbit diameter. In addition, O. flagris has shorter pelvic fin rays but longer caudal peduncle and third dorsal fin spine. Its morphological features, distribution, remarks and photo of species are given in this paper.